2014
DOI: 10.1136/annrheumdis-2013-204804
|View full text |Cite
|
Sign up to set email alerts
|

Arterial haemodynamics and coronary artery calcification in adult patients with juvenile idiopathic arthritis

Abstract: JIA patients with long-term active disease had altered arterial haemodynamics compared with controls in our study. PWV was mainly determined by increased DBP, a parameter that again was associated with JIA disease and treatment variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
3
16
0
6
Order By: Relevance
“…The strength of the study is the long-term follow-up over 29 years of this cohort that has been described in several publications [17–19, 46, 48]. There are however some limitations of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the study is the long-term follow-up over 29 years of this cohort that has been described in several publications [17–19, 46, 48]. There are however some limitations of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The three primary non-invasive techniques utilized are flow-mediated dilation, carotid intima-media thickness, and pulse wave velocity. These modalities are vascular measures of early atherosclerosis and several investigators have demonstrated these markers to be abnormal or significantly different in patients with JIA in comparison to control groups[17-21]. Coulson et al completed a recent review summarizing the literature available on this subject and concluded that while surrogate markers in JIA patients suggest cardiovascular abnormalities, there is an unclear relationship between long-term cardiovascular risk and JIA and further studies are necessary[12].…”
Section: Discussionmentioning
confidence: 99%
“…The participant group was comprised of a previously described cohort of 373 patients who were first referred to OUH from 1980 through 1985 and diagnosed with JRA[4, 15, 16]. Patients evaluated after a median of 29 years disease duration (170/373, 46%) were included in the study[6, 17]. Evaluation at 29 years consisted of one of the following: a mailed questionnaire about cardiovascular comorbidity/risk factors if the patient did not have active disease at prior 15 and 23 year follow-up (86/170; 51%), or an extended clinical exam with interview if the patient did have active disease at 15 and/or 23 year follow-up (84/170; 49%).…”
Section: Methodsmentioning
confidence: 99%
“…При про-спективном исследовании (средняя продолжительность 29 лет) пациентов с ЮИА, имевших признаки продол-жающейся активности заболевания, выявлено сохране-ние увеличенной артериальной жесткости, оцениваемой по скорости распространения пульсовой волны (pulse wave velocity, РWV), и связанное с этим повышение уровня диастолического артериального давления. Повышенная жесткость артерий и осложнения, связанные с ней (гипер-трофия левого желудочка, инсульт и инфаркт миокарда), наблюдаются в зрелом возрасте, тогда как истоки при-ходятся на детский/подростковый возрасты и характери-зуются доклинической и бессимптомной фазой, которая длится несколько десятилетий [93].…”
Section: эндотелиальная дисфункция при ювенильном идиопатическом артритеunclassified